To solve the equation \( \frac{1}{2}m + 7 = m + 15 \), we start from where you left off:
-
You multiplied both sides by 2 to eliminate the fraction: \[ 2 \times \left(\frac{1}{2}m + 7\right) = 2 \times (m + 15) \] This simplifies to: \[ m + 14 = 2m + 30 \]
-
Now, we can rearrange the equation to isolate \( m \). First, subtract \( m \) from both sides: \[ 14 = 2m - m + 30 \] This simplifies to: \[ 14 = m + 30 \]
-
Next, subtract 30 from both sides to solve for \( m \): \[ 14 - 30 = m \] Thus: \[ m = -16 \]
So the value of \( m \) is \( \boxed{-16} \).